Engineering the next generation of CAR T- cells: precision modifications, logic gates and universal strategies to overcome exhaustion and tumor resistance - Garcia-Robledo, Juan Esteban; Cabrera-Salcedo, Sergio; Brandauer, Andreas Michael; Romano, Francesco; Rengifo-Martinez, Joshua; Toro-Pedroza, Alejandro; Victoria, Juan Sebastián; Rios-Serna, Lady J.; Loukanov, Alexandre; Cardona, Andrés Felipe; Genovese, Pietro; Baena, Juan Camilo (Frontiers in Oncology, 2026)
Chimeric antigen receptor (CAR) T-cell therapy has transformed the treatment landscape of hematologic malignancies, delivering durable remissions in diseases previously associated with poor outcomes. However, translating this success to solid tumors has proven challenging due to antigen heterogeneity, limited tumor infiltration, immunosuppressive tumor microenvironments, and progressive T-cell exhaustion. In response, next-generation CAR T-cell platforms have emerged that integrate advances in receptor architecture, intracellular signaling, and programmable control systems to enhance specificity, persistence, and safety. This review comprehensively examines recent innovations in CAR T-cell engineering, including optimization of extracellular binding domains, hinge and transmembrane modifications, fine-tuning of intracellular signaling motifs, and the incorporation of alternative protein scaffolds. We discuss logic-gated strategies such as synNotch receptors, inducible ON-switch CARs, inhibitory CARs, and modular adaptor systems that enable context-dependent activation and reduce off-tumor toxicity. In parallel, we explore approaches aimed at overcoming T-cell dysfunction through intrinsic checkpoint rewiring, cytokine armoring, and epigenetic reprogramming to sustain antitumor activity in hostile microenvironments. The development of allogeneic and off-the-shelf CAR T-cell products derived from healthy donors, induced pluripotent stem cells, natural killer cells, γδ T cells, and macrophages is also reviewed, highlighting strategies to mitigate graft-versus-host disease and host immune rejection while enabling scalable manufacturing. Finally, we address current translational bottlenecks related to immunogenicity, regulatory complexity, and production logistics, and outline future directions for integrating Boolean logic circuits, safety switches, and automated GMP-compliant processes. Collectively, these advances position next-generation CAR T-cell therapies as programmable and adaptable immunotherapeutic platforms with the potential to extend durable clinical benefit beyond hematologic cancers into solid tumors.